Study of the Delignification Process of Green Algae (Chlorophyceae) for ?-Cellulose Production - Sulis Safaatin Hidayah; Shafa Alika Wulandari; Sintha Soraya Santi; Ketut Sumada; Ni Ketut Sari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Green algae (Chlorophyceae) are a lignocellulosic biomass with considerable potential as a source of ?-cellulose due to their relatively high cellulose content. This study aimed to produce ?-cellulose via alkaline delignification and to investigate the effects of NaOH concentration and delignification time on the resulting product's characteristics. The delignification process was carried out using NaOH concentrations ranging from 6% to 14% and delignification times of 30–90 min at 60°C. The resulting product were analyzed using the Chesson-Datta method and further characterized by FTIR and SEM analyses, while process optimization was performed using Response Surface Methodology (RSM). The results showed that the optimum conditions were achieved at an NaOH concentration of 8% and a delignification time of 45 min, yielding an ?-cellulose content of 51.2%, a hemicellulose content of 16.9%, and a lignin content of 5.4%. FTIR analysis confirmed the presence of functional groups characteristic of ?-cellulose, whereas SEM observations revealed morphological changes in the fiber surface, which became rougher and more porous due to the removal of lignin and hemicellulose. RSM optimization predicted optimum conditions yielding 51.234% ?-cellulose, 12.990% hemicellulose, and 4.963% lignin. Contribution to Sustainable Development Goals (SDGs): SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 14: Life Below WaterSDG 15: Life on Land